Polish Underground Extracts, no. 13 (1984) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Extracts from Polish underground publications compiled and translated into English by the RFE Polish Publication Unit for broadcasting purposes. Introductions to most articles are provided by RFE staff, and items are compiled in issues based mainly on theme and date. About Citizens' Committees Against Violence: An Interview with Jan Józef Lipski[from: Tygodnik Mazowsze, no. 108 (29 November 1984)]"Tygodnik Mazowsze," the major underground Solidarity paper for the Warsaw area, interviewed Jan Józef Lipski, a senior member of the former Workers' Defense Committee [Komitet Obrony Robotników (KOR)] on the subject of the new Citizens' Committees against Violence, which are being formed in several Polish cities in the wake of the murder of Father Jerzy Popiełuszko in order to monitor the abuse of human rights. Memories of Father Jerzy[from: Tygodnik Mazowsze, no.104 (1 November 1984)]The leading Solidarity weekly, published in Warsaw, published memories of Father Jerzy Popiełuszko from three ordinary people who had come into close contact with him: a foundry worker from the Warsaw Foundry, who, tellingly, calls him by his first name, without the usual "Father;" an altar boy from his parish church; and a miner from Silesia, who was a regular worshiper at the Masses for the Homeland. We Are All to Blame[from: Informacja, no. 36 (31 October 1984)]This statement was issued by the underground Solidarity Executive Committee for the Warsaw region on October 31 in response to the news of the murder of Father Jerzy Popiełuszko. The statement was reprinted by numerous underground publications, among them "Informacja" [Information], a newsletter published in Father Popiełuszko's parish church of St. Stanislaw Kostka in the Żoliborz district of Warsaw. Almost immediately after the news had broken about Popieluszko's abduction, "Informacja" started bringing out the latest news, sometimes with several issues a day, a detailed account of the priest's last day, statements issued by various groups, and several open letters of protest. Questions / by Jan Lityński[from: Tygodnik Mazowsze, no.104 (1 November 1984)]This is a commentary by Jan Lityński, a former KOR member and editor of "Robotnik" [The Worker], on the murder of Father Jerzy Popiełuszko. In 1981 Lityński was an advisor to Solidarity's Regional Boards in Wałbrzych, Lower Silesia, and Warsaw. Interned on 18 December 1981, Lityński, together with other leading members of KOR, was charged with preparing the violent overthrow of the state. In June 1983 Lityński failed to return to prison from a temporary parole and has been in hiding ever since. A Few Remarks on Church Policies / by K [from: Tygodnik Mazowsze, no. 106 (15 November 1984)]This article, published in the major Solidarity weekly for the Warsaw region, considers the pros and cons of the Church authorities' behavior following the death of Father Popiełuszko. It was signed with the letter "K," which may suggest that the article represents the views of the author alone and not the paper itself. Crime and Politics / by Jacek Kuroń[from: Tygodnik Mazowsze, no. 107 (22 November 1984)]One of the best known opposition activists speculates about the circumstances surrounding the murder of Father Jerzy Popiełuszko and its possible consequences. Jacek Kuroń's article, reflecting his personal opinions on the matter, appeared in a major underground weekly for the Warsaw area. Declaration of the Citizens' Committee Against Violence[from: Tygodnik Mazowsze, no. 106 (15 November 1984)]In response to the abduction and murder of Father Jerzy Popiełuszko, several groups have been set up in various Polish cities to monitor human rights in Poland. The groups declared their intention to act openly, the first such initiative since the imposition of martial law. Announcement of the Death of Father Jerzy Popiełuszko[from: Leaflet. Issued by Solidarność Walcząca (October 1984)]